Morphological variation in the common lancehead populations: Sexual dimorphism and ontogenetic patterns - Siqueira, L. H. C. [UNESP]; Piantoni, C.; Marques, O. A. [UNESP] (Wiley-Blackwell, 2022)
The common lancehead Bothrops jararaca is widespread in the Atlantic Forest in Brazil. The species is known to show a marked sexual dimorphism pattern, with the female being larger than the male. However, most efforts in clarifying morphological variation between the sexes are often focused on a single population. In this paper, we investigate how sexual dimorphism and ontogenetic trajectories vary among populations as well as the ontogenetic trajectories of B. jararaca. We analyzed 211 specimens from a coastal and a highland population and measured 17 morphological traits, including linear and meristic characteristics, and the analysis revealed a clear but variable effect of sex and population. Females were larger than males in all evaluated populations. Furthermore, females in the coastal population were generally smaller than in the highland population but had significantly more scales. Widespread species often experience differential environmental pressures even in terms of biotic and abiotic factors. We attribute the results found herein to specificities in prey availability and climatic conditions which affect the ontogenetic pattern between the sexes and the populations, resulting in specific sexual dimorphism patterns.
Keywords: Geographic variation; Allometry; growth; Morphometry; Bothrops jararaca; Snakes; Sexual dimorphism